COVID-19's impact on the cryptocurrency market and the digital economy - Mansour, Nadia, 1984-; Salem, Salha Ben, 1992- (Advances in finance, accounting, and economics (AFAE) book series., 2022)
"This book provides theoretical and empirical frameworks in the field of finance and technology for professionals who want to improve their understanding of the importance of blockchain, bitcoin, and the digital transformation in business"--